Organizational Strategy Orientation and Performance of Travel Agency Companies in Indonesia - Eko Purwanto; Muhadjir Anwar; Ayundha Evanthi (Future Science, 2022)
The present paper investigates the effect of entrepreneurial orientation (EO), market orientation (MO), and learning orientation (LO) on the performance of travel agency companies in Indonesia. The result suggests that EO has a significant direct effect on performance. Another findings are LO mediates the relationship between EO and MO and performance, also EO mediates the influence of MO on performance. The study offers a more detailed understanding of which organizational strategy orientation improves the performance of travel agency companies.